Reinterpreting the Eucharist : explorations in feminist theology and ethics - Hogan, Carol; Power, Kim; Elvey, Anne F. (Gender, theology, and spirituality., 2014)
The Eucharist continues to be central to contemporary Christian religious tradition and to be the focus for a wide range of assumptions and disputes. Chief amongst these disputes is the role of women in the theology and the ritual of the Eucharist. Reinterpreting the Eucharist brings together a diverse range of voices with each using their own marginalised experience to explore other ways - Indigenous culture, medieval and contemporary art, social history, and environmental ethics - of engaging with the Eucharist. Presenting new forms of theological and ethical engagement, the book responds to.